2021
DOI: 10.1200/jco.2021.39.15_suppl.5563
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of ovarian cancer patients treated with platinum or non-platinum based chemotherapy after PARP inhibitor maintenance.

Abstract: 5563 Background: PARP inhibitors (PARPi) are approved for maintenance treatment of platinum sensitive ovarian cancers either after front-line therapy or after treatment for recurrence. Current recommendations include retreatment with platinum-based chemotherapy (PC) after progression on maintenance PARPi. There exists a theoretical concern that progression of disease (POD) on PARPi is indicative of the development of platinum resistance due to similar DNA targets of platinum chemotherapy and PARPi. Our object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Our study has demonstrated that the time to first subsequent treatment is not altered by the intent of a prior PARP inhibitor, a finding that is similar to published literature 13. Though not all post PARP inhibitor randomized trials have explored this endpoint, it is notable that there was a decrease in time to first subsequent treatment in the cohorts from SOLO1 (51.8 months) and SOLO2 (27.9 months) 2 3…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our study has demonstrated that the time to first subsequent treatment is not altered by the intent of a prior PARP inhibitor, a finding that is similar to published literature 13. Though not all post PARP inhibitor randomized trials have explored this endpoint, it is notable that there was a decrease in time to first subsequent treatment in the cohorts from SOLO1 (51.8 months) and SOLO2 (27.9 months) 2 3…”
Section: Discussionsupporting
confidence: 86%
“…In our cohort, following PARP inhibitor progression, 73% and 27.3% of patients received platinum-based and non-platinum chemotherapy, respectively. This is similar to Brann et al ’s cohort of 83 patients previously receiving a maintenance PARP inhibitor, 29 patients subsequently received chemotherapy with 21 (72.4%) and 8 (27.6%) receiving platinum and non-platinum therapy, respectively 13. Similarly, in the SOLO2/ENGOT Ov-21 cohort, 51% and 53% of patients received platinum-based chemotherapy following progression on olaparib and placebo, respectively 14…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…These values are in line with those reported in our series, while adding locoregional treatment and continuing PARP inhibition. Relative to the median treatment time with PARPi, in the study by Brann et al38 this value was 9.0 and 5.5 months for platinum and non-platinum-based chemotherapy arms. The longer median treatment time with PARPi until oligometastatic progression in our series could be due to the high percentage of patients undergoing secondary cytoreductive surgery (47%) with complete cytoreduction (86%) before starting PARPi maintenance therapy, which has been shown to improve the effectiveness of PARPi as both first-line39 and second-line treatment 22–26…”
Section: Discussionmentioning
confidence: 92%
“…After Olaparib resistance, the ORR of platinum-based chemotherapy was 40% (19/48), and the median PFS was 22 weeks, suggesting that there was still a partial response to platinum-based chemotherapy after PARPi resistance. Another study found that both platinum and non-platinum chemotherapy had a response rate after resistance of PARPi maintenance therapy, with median PFS of 7.0 and 8.5 months, respectively 22 . In our study, the PFI was significantly prolonged after PARPi monotherapy, and the median TFST of subsequent platinum-based chemotherapy after PARPi resistance was 7.5 months, consistent with patients in control group with platinum-sensitive relapse after third-line platinum-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%